1989
DOI: 10.1093/carcin/10.7.1291
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cyclic 1, N2-propanodeoxyguanosine adducts in DNA of rats treated with N-nitrosopyrrolidine and mice treated with crotonaldehyde

Abstract: Cyclic 1,N2-propanodeoxyguanosine adducts are formed in vitro in DNA treated with alpha-acetoxy-N-nitrosopyrrolidine or its metabolite, crotonaldehyde. However, the in vivo formation of these cyclic adducts in DNA has not been demonstrated due to the lack of a sensitive detection method. In this study, a 32P-postlabeling method specific for the detection of 1,N2-propanodeoxyguanosine adducts was developed by using the corresponding 3'-monophosphates as standards. This method was validated by using DNA modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 0 publications
5
121
0
5
Order By: Relevance
“…We also obtained convincing evidence for the presence of N 6 -THF-dAdo (14) and N 4 -THF-dCyd (17) but quantitation was more difficult due to their low amounts and the presence of interfering peaks in some samples. Several lines of evidence support these conclusions.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We also obtained convincing evidence for the presence of N 6 -THF-dAdo (14) and N 4 -THF-dCyd (17) but quantitation was more difficult due to their low amounts and the presence of interfering peaks in some samples. Several lines of evidence support these conclusions.…”
Section: Discussionmentioning
confidence: 71%
“…A limitation of this study is the method of quantitation of N 2 -THF-dGuo (13), N 6 -THF-dAdo (14), and dThd adducts 15 and 16. While NaBH 3 CN treatment of DNA converts these adducts to the corresponding stable 4- (HOB)-adducts 18-21 Several previous studies of reactants other than α-acetoxyNPYR have demonstrated the in vitro formation of adducts resulting from the reaction of oxonium ions, lactols, or related intermediates with deoxyribonucleosides or DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that an analogous reaction of HNE with a protein lysine and a nucleic acid amine might represent a plausible pathway in the formation of DPCs. In addition, the detection of 1,N 2 -deoxyguanosine adducts of acrolein, crotonaldehyde, and 4-hydroxynonenal in human and rodent tissues, both as endogenous adducts and following chemical treatment (27)(28)(29)(41)(42)(43), may indicate that these stable DNA adducts exist as intermediates along a pathway of formation for DPCs. Consistent with such a mechanism, the results presented here demonstrate that peptide amines can react with these DNA adducts to form DNA-peptide cross-links via Schiff base linkage.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro wurden Proteinaddukte (Ichihashi et al 2001) und Histon-DNA-Crosslinks (Kuykendall und Bogdanffy 1992) durch Umsetzung mit 2-Butenal erzeugt. Nach Inkubation mit 2-Butenal ließen sich in isolierter Kalbsthymus-DNA, kultivierten CHO-Zellen und menschlichen Fibroblasten sowie lokal und systemisch in verschiedenen Geweben von in vivo behandelten Mäusen und Ratten zyklische 1,N 2 -Propanodesoxyguanosin-Addukte nachweisen, die als Folgeprodukte einer Michael-analogen Reaktion der aktivierten C-C-Doppelbindung des 2-Butenals mit dem exozyklischen Stickstoff des Desoxyguanosin-Rests aufzufassen sind (Budiawan und Eder 2000;Chung et al 1988Chung et al , 1989Eder et al 1999;Foiles et al 1990;Wilson et al 1991). Zyklische 1,N 2 -Propanodesoxyguanosin-Addukte werden in vivo in Tier und Mensch auch endogen gebildet (Chung et al 1999(Chung et al , 2003.…”
Section: Wirkungsmechanismusunclassified